2016
DOI: 10.1111/aec.12334
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term patterns of invertebrate abundance and relationships to environmental factors in arid Australia

Abstract: Resource pulses are a key feature of semi-arid and arid ecosystems and are generally triggered by rainfall. While rainfall is an acknowledged driver of the abundance and distribution of larger animals, little is known about how invertebrate communities respond to rain events or to vegetative productivity. Here we investigate Ordinal-level patterns and drivers of ground-dwelling invertebrate abundance across 6 years of sampling in the Simpson Desert, central Australia. Between February 1999 and February 2005, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
68
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 75 publications
3
68
1
Order By: Relevance
“…Indeed, long‐term surveys of invertebrates in our study region have revealed little effect of short‐term rainfall on invertebrate activity, but disparate effects at different spatial scales between invertebrate taxa up to 18 months after rain (Kwok et al. ). It is thus possible that both N. ridei and S. youngsoni were responding to site‐specific temporal differences in their prey.…”
Section: Discussionmentioning
confidence: 89%
“…Indeed, long‐term surveys of invertebrates in our study region have revealed little effect of short‐term rainfall on invertebrate activity, but disparate effects at different spatial scales between invertebrate taxa up to 18 months after rain (Kwok et al. ). It is thus possible that both N. ridei and S. youngsoni were responding to site‐specific temporal differences in their prey.…”
Section: Discussionmentioning
confidence: 89%
“…, Kwok et al. ). Additionally, vegetation dynamics in Kinchega are known to be driven by both higher winter rain, which favors growth of annual plants, and higher summer rain, which immediately induces flowering in perennial plants (Robertson et al.…”
Section: Discussionmentioning
confidence: 99%
“…) could affect the vegetation and arthropod development (Kwok et al. ) in arid Australia, we also considered an interaction between each water‐related parameter and summer temperature. For comparison, we performed LMMs using direct distant (i.e., ENSO) climatic predictors.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to Kwok et al. (), our study was conducted in arid shrubland dominated by fine‐textured soil, which can hold moisture longer than coarse sandy soil and is more able to retain basic nutrients such as carbon, nitrogen, and phosphorous, which are important to microbe and plant growth (Austin et al. , Nano and Pavey ).…”
Section: Discussionmentioning
confidence: 89%
“…, Kwok et al. ). If the small rain event documented in our study was not sufficient to cause an increase in plant productivity, this may explain the lack of a positive response from larger herbivorous insects such as crickets and hemipterans, which only displayed responses to longer‐term changes in rain.…”
Section: Discussionmentioning
confidence: 99%